Styles family education: domestic and foreign classification - Kuzmishina T.L.; Amelina E.S.; Permyakova A. A.; Khokhlova E.A. (Современная зарубежная психология, 2015)
National and foreign literature includes many works, describing various types of family education. In these works, classification is ordinarily based on author-related criteria. Thus, it seems next to impossible to single out a unified classification of family education styles. This article is an attempt to regard different criteria of estimating family education